Overexpression of ACTL6A is associated with poor prognosis in gastric cancer, and nuclear level is an independent predictor - Wang, Qiqi; He, Haihong; Zhou, Yiwen; Li, Peng; Huang, Tingting (Translational Cancer Research, 2026)
Gastric cancer (GC) is a heterogeneous disease with limited prognostic biomarkers. ACTL6A is a core subunit of chromatin remodeling complexes, is implicated in tumor progression, but its clinical relevance, particularly subcellular localization, in GC remains unclear. This study aims to investigate whether the subcellular distribution of ACTL6A can serve as a potential biomarker for prognosis assessment in patients with GC.